2003
DOI: 10.1002/jms.528
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of negative ions in atmospheric pressure photoionization conditions

Abstract: Atmospheric pressure photoionization (APPI) 1 is a new technique, highly interesting for its features, mainly selectivity and sensitivity, somehow overlapping the performances of the well-established electrospray (ESI) 2 and atmospheric pressure chemical ionization (APCI) 3 techniques. The basic principle of this method is, at first sight, very simple: a molecule M can be ionized by interaction with a photon beam only if its ionization energy (IE) is lower, or equal to, the photon energy h :Hence the irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 7 publications
1
38
1
1
Order By: Relevance
“…Kostiainen et al studied negative ion formation mechanisms by investigating ionization efficiency and ion type (even-or odd-electron ion) for analytes of different polarity in various solvents [3,7]. Traldi et al reported negative ion formation by resonant electron capture from thermal electrons originating from metal surfaces and dopant [8].…”
Section: And [M ϩ D]mentioning
confidence: 99%
“…Kostiainen et al studied negative ion formation mechanisms by investigating ionization efficiency and ion type (even-or odd-electron ion) for analytes of different polarity in various solvents [3,7]. Traldi et al reported negative ion formation by resonant electron capture from thermal electrons originating from metal surfaces and dopant [8].…”
Section: And [M ϩ D]mentioning
confidence: 99%
“…35 42,43 Negative-ion APPI has been studied through the investigation of its ionization mechanism by Kostiainen and co-workers 5,44 and Traldi and co-workers. 45 Although both Kostiainen and co-workers 5,44 and Traldi and co-workers 45 demonstrated the feasibility of ionization of less polar compounds by negative-ion APPI, only the analysis of polybrominated diphenyl ethers containing more than five bromine atoms proved to be superior to other API modes. 7,8 In a recent review on APPI, 2 Karst and co-workers stated that ''the ionization mechanism is probably the main issue here'' and that ''the solvent plays a much larger role in the analyte ionization, whereas the electron-ejection and electron-capture theory is less applicable than first expected, making the method less promising for low polarity analytes''.…”
mentioning
confidence: 97%
“…In dopant assisted negative ion-APPI, the ionization process is initiated by thermal electrons. Currently, subsequent ionization mechanisms including EC, dissociative EC, and proton transfer are suggested to be responsible for the formation of negative ions [8,10,11]. In this study, nitroaromatics were preliminarily chosen as analytes because previous studies demonstrated multiple ionization products by both EC-NICI [12,13] and EC-APCI [14 -19].…”
mentioning
confidence: 99%